Pelatihan Pembuatan Handmade Soap Bar dan Cara Memulai Bisnisnya di Tambaksogra, Sumbang, Banyumas - Desy Nawangsari; Rani Prabandari; Puspita Lianti Putri (Journal of Social Responsibility Projects by Higher Education Forum, 2023)
Soap is one of the cosmetic products that is definitely needed in household life. Most cleaning products, including soap, contain additives in the form of surfactants. Surfactants are used to lower the interfacial tension, so dirt can be removed from the skin. Sodium Lauryl Sulfate (SLS) is a surfactant that is commonly found in cleaning products. The use of surfactants for households produces waste that will enter the environment. The presence of surfactants in the environment in large concentrations can disrupt ecosystems such as the foam generated by surfactants can reduce dissolved oxygen concentrations, can accumulate in the bodies of aquatic organisms and can interfere with the reproductive processes of aquatic organisms. Sumbang District is located in a 4.4 km radius from the Harapan Bangsa University Campus. The target of this service partner is the non-productive economic community, in the form of one of the PKK groups in Tambaksogra Village working as a Housewife (IRT) and has no income with the latest educational background senior high school. The objectives of this activity are (1) to increase knowledge and increase skills in making environmentally friendly solid soap (2) to reduce waste from surfactants produced by soap on the market (3) to produce soap products and provide an overview of how to start a business. The results of this community service activity showed that there was an increase in the participants' knowledge from 37.5% to 91.25%, participants acquired the skills of making handmade soap bars. The discussion session during the provision of education regarding the current business strategy was greeted enthusiastically by the activity participants.